Forecasting tourist arrivals using origin country macroeconomics. Issue 27 (8th June 2016) - Chatziantoniou, Ioannis; Degiannakis, Stavros; Eeckels, Bruno; Filis, George
ABSTRACT: This study utilizes both disaggregated data and macroeconomic indicators in order to examine the importance of the macroeconomic environment of origin countries for analysing destinations' tourist arrivals. In particular, it is the first study to present strong empirical evidence that both of these features in tandem provide statistically significant information of tourist arrivals in Greece. The forecasting exercises presented in our analysis show that macroeconomic indicators conducive to better forecasts are mainly origin country-specific, thus highlighting the importance of considering the apparent sharp national contrasts among origin countries when investigating domestic tourist arrivals. Given the extent of the dependency of the Greek economy on tourism income and also the perishable nature of the tourist product itself, results have important implications for policymakers in Greece.